Human Mental Models of Humanoid Robots - LEE, Sau-Lai (Institutional Knowledge at Singapore Management University, 2005)
Effective communication between a person and a robot may depend on whether there exists a common ground of understanding between the two. In two experiments modelled after human-human studies we examined how people form a mental model of a robot's factual knowledge. Participants estimated the robot's knowledge by extrapolating from their own knowledge and from information about the robot's origin and language. These results suggest that designers of humanoid robots must attend not only to the social cues that robots emit but also to the information people use to create mental models of a robot.